2024
DOI: 10.3390/ijms25042116
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG Laser Alleviates Inflammaging in Diabetes-Associated Periodontitis via Activation CTBP1-AS2/miR-155/SIRT1 Axis

Min Yee Ng,
Cheng-Chia Yu,
Szu-Han Chen
et al.

Abstract: Periodontitis is a significant health concern for individuals with diabetes mellitus (DM), characterized by inflammation and periodontium loss. Hyperglycaemia in DM exacerbates susceptibility to periodontitis by inducing inflammaging in the host immune system. The use of erbium-doped yttrium–aluminum–garnet laser (ErL) in periodontitis treatment has gained attention, but its impact on diabetic-associated periodontitis (DP) and underlying mechanisms remain unclear. In this study, we simulated DP by exposing hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…LncRNAs play a pivotal role in periodontitis and there is growing evidence that lncRNAs have diagnostic value. Wu et al found that inflammation in diabetes-associated periodontitis can be attenuated by activating the CTBP1-AS2/miR-155/SIRT1 axis ( Ng et al, 2024 ). Xia et al found that long-chain non-coding RNA PVT1 can be involved in pulpitis pathogenesis by regulating miR-128-3p ( Xia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs play a pivotal role in periodontitis and there is growing evidence that lncRNAs have diagnostic value. Wu et al found that inflammation in diabetes-associated periodontitis can be attenuated by activating the CTBP1-AS2/miR-155/SIRT1 axis ( Ng et al, 2024 ). Xia et al found that long-chain non-coding RNA PVT1 can be involved in pulpitis pathogenesis by regulating miR-128-3p ( Xia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus production involved co-transfection of the plasmid DNA mixture with the lentivector and helper plasmids (VSVG and Gag-Pol) into 293T cells (ATCC, Manassas, VA, USA) using Lipofectamine 2000 (LF2000, Invitrogen) according to the manufacturer's protocol. 13 Unless explicitly stated otherwise, the transfection reagent used in following experiments was Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences used were: α-SMA (forward: 5′-AGCACATGGAAAAGATCTGGCACC-3′, reverse: 5′-TTTTCTCCCGGTTGGCCTTG-3′), COL1A1 (forward: 5′-GGGTGACCGTGGTGAGA-3′, reverse: 5′-CCAGGAGAGCCAGAGGTCC-3′), and GAPDH (forward: 5′-CTCATGACCACAGTCCATGC-3′, reverse: 5′-TTCAGCTCTGGGATGACCTT-3′). 13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations